Implementasi Media Pembelajaran Word Wall Dalam Meningkatkan Hasil Belajar Siswa Mata Pelajaran IPS - Riska Noor Oktaviani; Aida Lathifa Mumtaza; Dany Miftah M. Nur (RUKASI: Jurnal Ilmiah Perkembangan Pendidikan dan Pembelajaran, 2025)
The use of innovation learning media is crucial for enhancing student learning outcomes, especially in social studies subjects. Word Wall, as a digital platform, offers various interactive and engaging learning activities, enabling students to actively participate in the learning process. This research aims to examine the effectiveness of Word Wall in improving student learning outcomes. The method used is qualitative research with a descriptive approach. The results indicate that the implementation of Word Wall positively contributes to increasing students understanding and engagement while catering to diverse learning styles. However, challenges in its implementation include the digital divide among students.